2014
DOI: 10.1016/j.jcte.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The value of neck circumference (NC) as a predictor of non-alcoholic fatty liver disease (NAFLD)

Abstract: AimsTo analyze the correlation between neck circumference (NC) and non-alcoholic fatty liver disease (NAFLD) and compare the predictive value of NC for NAFLD with that of other simple anthropometric measures and other biochemical profiles.Methods2761 subjects, undergoing a medical check-up at the Changhai Hospital between October 01, 2012 and November 30, 2012, were recruited to the study. NC, other simple anthropometric measures, and biochemical profiles were analyzed.ResultsNC in NAFLD subjects with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
(29 reference statements)
4
24
0
Order By: Relevance
“…In this context, neck circumference (NC) consists of a rapid, viable and low cost evaluation. The use of NC as an anthropometric indicator not influenced by variations in certain health conditions, that cause abdominal distension, for example, or by respiratory movements, reinforces the use of this measure as an indicator that provides consistent results to predict the deposition of subcutaneous fat (8) in the upper region of the body, and with the liver fat deposit, consequently, with NAFLD (8,9) .…”
Section: The Correlation Of Neck Circumference and Insulin Resistancementioning
confidence: 70%
See 1 more Smart Citation
“…In this context, neck circumference (NC) consists of a rapid, viable and low cost evaluation. The use of NC as an anthropometric indicator not influenced by variations in certain health conditions, that cause abdominal distension, for example, or by respiratory movements, reinforces the use of this measure as an indicator that provides consistent results to predict the deposition of subcutaneous fat (8) in the upper region of the body, and with the liver fat deposit, consequently, with NAFLD (8,9) .…”
Section: The Correlation Of Neck Circumference and Insulin Resistancementioning
confidence: 70%
“…In order to evaluate the relationship between NC and NAFLD, a study by Hu et al (9) evaluated 2.761 chinese and identified that patients with NAFLD with an alteration in glutamic pyruvic transaminase presented NC of 38.94±2.62 cm and patients without alteration presented NC of 37.21±3.06 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is becoming a worldwide epidemic and one of the most important global health issues. 25 NAFLD is associated with metabolic syndrome (MS), including obesity, hyperlipidemia, hypertension, and diabetes. Therefore, NAFLD is considered part of MS. 26 , 27 , 28 Several genes have been identified as potential candidates in the pathogenesis and progression of fatty liver, genes involved in mechanisms of liver injury and genes influencing lipid metabolism like microsomal triglyceride transfer protein (MTP).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that fat in the neck may be more similar to visceral fat, which is more strongly related with cardiometabolic risks compared to subcutaneous fat [ 9 ]. An increase in neck circumference has even been found to be an independent predictor of nonalcoholic fatty liver disease [ 20 22 ]. Although studies have shown associations between neck circumference and components of metabolic syndrome, more studies directly comparing neck circumference with other anthropometric measures are needed, as neck circumference is not included in standard guidelines and practices and is not generally included in research studies or clinical assessments [ 23 , 24 ], even in situations when waist circumference may not be feasible or meaningful.…”
Section: Introductionmentioning
confidence: 99%